PERAN E-GOVERNMENT DALAM MENINGKATKAN TRANSPARANSI PUBLIK DI INDONESIA (STUDI KASUS PADA PEMERINTAH KABUPATEN BANDUNG) - Kristian, Indra; Nuradhawati, Rira; Ristala, Harky (Universitas Jenderal Ahmad Yani, 2024)
Implementing e-government has become an important strategy in increasing public transparency in the digital era. This research aims to analyze the role of e-government in increasing public transparency in the Bandung Regency Government. Using a descriptive qualitative approach, data was collected through in-depth interviews with government officials, public service users, as well as observations of official websites and e-government applications used in Bandung Regency. The research results show that the implementation of e-government in Bandung Regency has succeeded in increasing access to public information, speeding up administrative services, and increasing local government accountability. However, there are a number of obstacles faced, such as limited technological infrastructure and human resource capacity. The implications of this research indicate that strengthening information technology systems and increasing human resource capacity through intensive training is necessary to optimize the implementation of e-government in supporting public transparency. This research makes a significant contribution to understanding the relationship between e-government and transparency at the local government level, as well as offering relevant policy recommendations.